Familial Interstitial Pulmonary Fibrosis: A Large Family with Atypical Clinical Features - Ranji Chibbar; John A Gjevre; Francis Shih; Heather Neufeld; Edmond G Lemire; Derek A Fladeland; Donald W Cockcroft (Canadian Respiratory Journal)
A large kindred of familial pulmonary fibrosis is reported. Six members from the first two generations of this particular kindred were described more than 40 years previously; six more individuals from the third and fourth generations have also been evaluated. The proband, now 23 years of age, has mild disease; the other 11 documented affected family members all died from their disease at an average age of 37 years (range 25 to 50 years). The pathology was that of usual interstitial pneumonia, as is typical in idiopathic pulmonary fibrosis. However, the initial radiographic pattern in many of these individuals was upper lobe and nodular and, along with the young age, was atypical for idiopathic pulmonary fibrosis. Several genetic abnormalities have been associated with familial pulmonary fibrosis. The present study examined the genes coding for surfactant protein-C, ATP-binding cassette protein A3 and telomerase, and found no abnormalities.